Gynecomastia: an uncommon, destabilizing condition of the male adolescent. our therapeutic choice - Pinelli, Massimo; De Maria, Federico; Ceccarelli, Pierluca; Pedrieri, Barbara; Bianchini, Maria Anastasia; Iughetti, Lorenzo; De Santis, Giorgio (Acta Biomedica Atenei Parmensis, 2023)
Gynecomastia is the benign enlargement of breast’s the glandular tissue in male population. Gynecomastia can involve fatty and/or glandular tissue. At the basis of pediatric gynecomastia there is a multifactorial imbalance in the ratio of estrogen to androgens tissue levels. In more than 95% of the cases gynecomastia development is idiopathic. Secondary causes of gynecomastia in adolescents are relatively rare (less than 5%) and may arise from uncommon pathological conditions. Gynecomastia is self-limited and regresses in 1-3 years in 84%, 47% and 20% of adolescents with mild, moderate and severe gynecomastia. The correct first line of therapy is observation and reassurance in the treatment of mild cases. In order to manage adolescent gynecomastia is advised to adopt a tailored therapy. Despite gynecomastia is a common condition only few adolescents need cosmetic or antalgic treatment. Medical therapy should be considered in patient with emotional distress or psychological limitation on normal activities. Finally, if gynecomastia does not go in remission after two years surgical procedures should be performed. The aim of this article is to be an updated discussion of pubertal gynecomastia in every way and report our surgical experience with a retrospective study. In conclusion surgical treatment of this condition is a quiet rare procedure but, in according to global literature we demonstrated that it is a safe surgery with low rate of complications.